Sami Rights in Finland’s Climate Act: Implementing a Human Rights-Based Approach - Hansen, Leena (Journal of Northern Studies, 2025)
This article concerns climate change and its alarming, accelerating consequences and impacts on human rights—in particular, the rights of persons and groups, such as Indigenous peoples, in unique, vulnerable situations. The rights of the Sami people are threatened by effects of climate change as well as resource and energy developments aimed at addressing climate change in the name of green transition—a situation similar to that of many Arctic Indigenous peoples. Indigenous peoples, including the Sami, have demanded justice and adoption of a human rights-based approach as acknowledged in the Paris Agreement, with respect to their rights, in climate change mitigation and adaptation measures. The scope of this article is to study, in the context of Finland’s new Climate Act (2022), the national implementation of the international framework of a justice and human rights-based approach, in relation to the Sami people’s rights recognized in Finland’s Climate Act and climate policies.